Growth Empirics with Institutional Measures and its Application to Transition Countries: A Survey - Luc Moers (Tinbergen Institute, 1998)
Institutions are strikingly absent from most economic theory, certainly from growth theory.In standard theory it is simply assumed that the needed institutional environment is there,within which economic agents can make their optimizing decisions. At the same time, indescriptive growth studies, particularly in economic history and most influentially inNorth (1990), the importance of good institutional contract enforcement has been emphasizedfor long. Good institutions guarantee property rights and minimize transaction costs,creating an environment conducive to economic growth. The considerable sunk costs of mostinvestments create large disincentives against binding resources to projects in an uncertain institutional environment.Until recently, empirical studies measuring just how important institutions are for growthand investment have been scarce. This has mainly been due to a lack of data concerning thequality of institutions. It is obviously impossible to find data which totally conforms toa most broad definition of institutions such as Schmieding's (1993, p. 233), stating thatthey '... encompass not only bureaucracies and administrations but also, and moreimportantly, the entire body of formal laws, rules and regulations as well as theinformal conventions and patterns of behavior that constitute the non-budget constraintsunder which economic agents can pursue their own individual ends'. Nevertheless, there hasincreasingly been data around which at least describes specific aspects of this definition,which covers both 'rule of law', or 'formal' institutions (enforced by the state), and'civil society', or 'informal' institutions (enforced by convention). This data has beenused to construct measures of the quality of institutions which have been applied in(cross-country) growth empirics. The initial studies have proxied the quality ofinstitutions indirectly, using universally observable and thus 'objective' measures.Recently some studies have used more direct ways to try and capture the quality ofinstitutions, using survey and thus 'subjective' measures.In this paper the most important empirical studies on the relationship betweeninstitutions and growth and investment, and the applications to transition countries,will be surveyed. A special focus on transition countries is considered justifiable,mainly because the transition process seems to a large extent about institutionaltransformation, so it may be expected that institutions 'matter' here in particular.In section 1 the main problems in (cross-country) growth empirics will be treated,showing as an important aside which (economic) variables have been found to be robustlyrelated to growth and investment. Section 2 and 3 will judge the empirical relevancefor growth and investment of respectively the objective and subjective institutionalmeasures which have been used in the literature. The to my knowledge only two studiesto date which have, in this context, specifically looked at transition countries willbe treated in section 4. Section 5 will conclude.
Keywords: 330; Institutionalismus; Wirtschaftswachstum; Investition; Systemtransformation; Übergangswirtschaft; Theorie